Caffeine promotes angiogenesis through modulating endothelial mitochondrial dynamics - Wang Li-tao; He Peng-cheng; Li An-qi; Cao Kai-xiang; Yan Jing-wei; Guo Shuai; Jiang Lei; Yao Lin; Dai Xiao-yan; Feng Du; Xu Yi-ming; Tan Ning (Acta Pharmacologica Sinica, 2021)
Caffeine induces multiple vascular effects. In this study we investigated the angiogenic effect of physiological concentrations of caffeine with focus on endothelial cell behaviors (migration and proliferation) during angiogenesis and its mitochondrial and bioenergetic mechanisms. We showed that caffeine (10–50 μM) significantly enhanced angiogenesis in vitro, evidenced by concentration-dependent increases in tube formation, and migration of human umbilical vein endothelial cells (HUVECs) without affecting cell proliferation. Caffeine (50 μM) enhanced endothelial migration via activation of cAMP/PKA/AMPK signaling pathway, which was mimicked by cAMP analog 8-Br-cAMP, and blocked by PKA inhibitor H89, adenylate cyclase inhibitor SQ22536 or AMPK inhibitor compound C. Furthermore, caffeine (50 μM) induced significant mitochondrial shortening through the increased phosphorylation of mitochondrial fission protein dynamin-related protein 1 (Drp1) in HUVECs, which increased its activity to regulate mitochondrial fission. Pharmacological blockade of Drp1 by Mdivi-1 (10 μM) or disturbance of mitochondrial fission by Drp1 silencing markedly suppressed caffeine-induced lamellipodia formation and endothelial cell migration. Moreover, we showed that caffeine-induced mitochondrial fission led to accumulation of more mitochondria in lamellipodia regions and augmentation of mitochondrial energetics, both of which were necessary for cell migration. In a mouse model of hindlimb ischemia, administration of caffeine (0.05% in 200 mL drinking water daily, for 14 days) significantly promoted angiogenesis and perfusion as well as activation of endothelial AMPK signaling in the ischemic hindlimb. Taken together, caffeine induces mitochondrial fission through cAMP/PKA/AMPK signaling pathway. Mitochondrial fission is an integral process in caffeine-induced endothelial cell migration by altering mitochondrial distribution and energetics.